Bioremoval of Zinc Using the Tomato Plant, Lycopersicon esculentum - Yamuna, Devi S; Surendran, A; Thatheyus, A.J (Journal of Public Health International, 2020)
Effluents discharged from various industries contain heavy metals. They reach the environment and affect the quality of air, water and soil. Though they are needed in trace quantities for living organisms, they become toxic when they exceed the threshold concentrations. Hence the present study has been designed to test the efficiency of Lycopersicon esculentum in removing zinc from soil. The tomato plants were grown in soil applied with 100, 200, 300, 400 and 500ppm of zinc sulphate for 60 days. Every fortnight, soil samples were taken and analysed for the levels of Cu, Zn, Fe and Mn. Percent removal of zinc by the plant was calculated from the residual concentration. More removal was noticed in higher concentrations of zinc. After 60 days of treatment, levels of Cu, Zn, Fe and Mn were analysed in the above ground and below ground parts of the tomato plant. Zinc level was 90 ppm in both cases and the same in plants grown in all the concentrations of zinc sulphate. Fluctuations in chlorophyll content were noticed while decline was observed in microbial colonies. The data were subjected to two way analysis of variance and the results are discussed. Graphical Abstract
Keywords: Phytoremediation; Plants; Heavy metals; Zinc; Tomato plant